Ablation spot area and impulse characteristics of polymers induced by burst irradiation of 1 µm laser pulses. (July 2017) - Tsuruta, Hisashi; Dondelewski, Oskar; Katagiri, Yusuke; Wang, Bin; Sasoh, Akihiro
Abstract: The ablation spot area and impulse characteristics of various polymers were experimentally investigated against burst irradiation of Nd: YLF laser pulses with a pulse repetition frequency of 1 kHz, wavelength of 1047 nm, temporal pulse width of 10 ns, and single-pulse fluence of 6.1 J/cm 2 to 17.1 J/cm 2 . The dependences of ablation area on the pulse energy from 0.72 to 7.48 mJ and the number of pulses from 10 pulses to 1000 pulses were investigated. In order to characterize their impulse performance as a function of fluence, which should not depend on ablation material, an effective ablation spot area was defined as that obtained against aluminum, 1050 A, as the reference material. An impulse that resulted from a single burst of 200 pulses was measured with a torsion-type impulse stand. Various impulse dependences on the fluence, which were not readily predicted from the optical properties of the material without ablation, were obtained. By fitting the experimentally measured impulse performance to Phipps and Sinko's model in the vapor regime, the effective absorption coefficient with laser ablation was evaluated, thereby resulting in three to six orders of magnitude larger than that without ablation. Among the polymers examined using polytetrafluoroethylene (PTFE) as the best volume absorbers, the highest momentum coupling coefficient of 66 μNs/J was obtained with an effective absorption coefficient more than six times smaller than that of the other polymers. Highlights: The burnt surface on aluminum shows excellent reproducibility of laser spot area. Laser ablation impulse performance of polymers exhibited strong material dependence. The momentum coupling coefficient, C m, of polymers exceeded the maximum of aluminum. An effective absorption coefficient during ablation is dominant for C m .